Factors influencing consumer behaviour in making online hotel reservation / Nur Ain Mohd Rosli - Mohd Rosli, Nur Ain (2018)
The research intends is to investigate the factors influencing consumer behaviour in making online hotel reservation. The hotel industry is profited from the fast expanded of ecommerce. Hotel reservations have ordinarily positioned high as a standout amongst the most popular items purchased through online. Online is a popular alternative for the travellers due to the nature of the business. Consumer now can have greater access to the information about the hotels. Hence, In the growing online market, hotel still looking and searching for the proficient method and efficient way to encourage and convince traveler to book room directly through hotel website. The methodology used in this research is quantitative. The target of respondents in this study are people that stay Around Kuala Lumpur. In addition, are 120 Sets Of questionnaire were distributed using simple random sampling technique. The data that have collected are analyzed using Statistical for Social Science (SPSS) version 22. Then Internal Reliability test and regression analysis are conducted. There are three independent variables which are price, trust and convenience and dependent variable is consumer behaviour in making online hotel reservation. In this research, results shows- that the independent variable Which is convenience and price are significantly influence consumer behaviour in making online hotel reservation. On the other hand, independent variable which is trust do not significantly influence on consumer behaviour. Lastly, the limitation involve with this research project were identified and recommendation also provided in this research. This finding can give company an insight on how to encourage customer using Website to make an online reservation.